Trauma and Emergency Surgery The Role of Damage Control Surgery - Tsoulfas, Georgios; Meshkini, Mohammad (IntechOpen, 2021)
One of the most interesting and challenging fields of surgery is trauma and emergency surgery. The formation of a trauma surgical subspecialty has led to a more organized system of dealing with trauma as well as saving lives. Emergency surgery has been the evolution of this, as an effort to incorporate the knowledge and skills of trauma surgery, intensive care, and emergency general surgery, all in one specialty. This is a collection of chapters describing the nature of damage control surgery, which is one of the key concepts and strategies for managing the most challenging trauma and emergency surgery patients. The authors of this book represent a team of true global experts on the topic. In addition to the knowledge shared, the authors provide their personal clinical experience in a variety of different aspects of damage control surgery.